High-elastic graphene-based metamaterial and preparation method thereof

By using a fluid subdividing device during the wet extrusion process, a superstructure of C-shaped graphene sheet arrangement is formed, and material performance is optimized through reduction treatment and high-temperature treatment, the problem of insufficient mechanical and elastic properties of graphene materials in the prior art is solved, and a high elastic and high-strength graphene-based metamaterial is realized.

CN119774595APending Publication Date: 2025-04-08ZHEJIANG UNIV

Patent Information

Application Number
CN202510031864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the spatial arrangement of graphene oxide/graphene to form a molecular-level superstructure, and graphene materials have shortcomings in mechanical properties and elastic properties.

Method used

The fluid subdivision device is introduced during the wet extrusion process. Through the fluid subdivision device composed of multiple horizontal grid plates, the arrangement and orientation of the graphene sheet layers are accurately controlled to form a superstructure of the arrangement of C-shaped graphene sheets, and the structure and performance of the material are further optimized through reduction treatment and high-temperature treatment.

Benefits of technology

It significantly improves the mechanical properties and rebound properties of graphene materials, forming high elastic and high-strength graphene-based metamaterials, suitable for high-performance applications such as piezoresistive stress sensors and high-performance composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774595A_ABST
    Figure CN119774595A_ABST
Patent Text Reader

Abstract

The invention discloses a high-elastic graphene-based metamaterial and a preparation method thereof.The preparation method comprises the steps that a graphene oxide solution is processed through a wet method and extruded through a large-size flow channel, blocky graphene oxide hydrogel is obtained, a fluid subdivision device is additionally arranged in front of a solution spraying opening, graphene oxide sheets generate a velocity gradient difference when subjected to subdivision multi-flow-field shearing, and the high-elastic graphene-based metamaterial is obtained; graphene oxide hydrogel with C-shaped superstructure arrangement is obtained by rearranging a graphene oxide lamellar texture, and the high-elasticity graphene-based metamaterial is obtained after freeze drying and reduction treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of graphene material preparation, and in particular to a highly elastic graphene-based metamaterial and a preparation method thereof. Background Art

[0002] Graphene has attracted extensive attention in the field of nanomaterials due to its excellent physical and chemical properties. As a two-dimensional material with a single layer of carbon atoms tightly arranged in a honeycomb lattice structure, graphene has extremely high strength, excellent electrical conductivity and thermal conductivity. These properties make graphene have broad application prospects in the fields of electronics, energy, sensors and composite materials. Metamaterials are a class of artificial materials with special properties, usually formed by a periodic arrangement of structural units, showing unique properties. Therefore, assembling graphene into superstructures with specific periodic unit arrangements is a current hot research direction. However, it is a major challenge for current research to effectively assemble single-layer graphene sheets into bulk materials with macroscopic sizes and specific molecular assembly superstructures while maintaining their excellent mechanical properties and resilience.

[0003] In order to solve these problems, researchers have proposed many methods, such as 3D printing, which is to print a superstructure with periodic arrangement in three-dimensional space by extrusion of graphene oxide slurry, and laser engraving technology, which directly carves out a supermaterial with periodic structure from graphene aerogel. However, the basic skeleton unit of graphene metamaterials prepared by these methods is graphene aerogel or aerogel fiber, which makes it difficult for graphene to exert its excellent performance. In addition, solution self-assembly can regulate the self-assembly behavior of graphene sheets by changing the pH value, ionic strength of the solution or adding different surfactants, thereby forming a graphene aerogel material with a specific structure; template-assisted assembly, using a specific template to arrange graphene sheets on the template surface according to a predetermined structure by deposition or growth. The shape and size of the template can accurately regulate the arrangement of graphene sheets to form a specific structure, such as a relatively simple ordered layered structure or a three-dimensional porous structure. However, the current method still finds it difficult to accurately control the spatial arrangement of graphene oxide / graphene to form a superstructure at the molecular level. Summary of the invention

[0004] In view of the above problems, the present invention proposes a highly elastic graphene-based metamaterial and a preparation method thereof, which overcomes the deficiencies of the mechanical and elastic properties of graphene materials in the prior art. The structure of traditional aerogels is usually loose, the arrangement of graphene sheets is very disordered, and they lack sufficient rigidity and stability to resist external stress. The present invention introduces a fluid subdivision device for the first time in the wet extrusion process to accurately control the arrangement and orientation of graphene sheets and prepare a graphene superstructure formed by C-shaped graphene sheets.

[0005] One of the technical solutions of the present invention is to provide a highly elastic graphene-based metamaterial, comprising a plurality of structural units, wherein the structural units have an arched structure formed by stacking curved graphene sheets in a lateral direction; the structural units are stacked up and down and fused with each other at the interface.

[0006] When subjected to shock or vibration, the curved graphene sheet can absorb some of the energy by bending slightly, and then release this energy when unloading, playing a certain buffering role. As long as the deformation remains within the linear elastic range, the curved graphene sheet can effectively store and release energy, showing good recovery ability.

[0007] The second technical solution of the present invention is to provide a graphene-based metamaterial as described above, which specifically includes the following steps: (1) a fluid subdivision device is provided in front of the fluid ejection port, a graphene oxide solution is wet-extruded through the fluid subdivision device, and then pushed into a coagulation bath to obtain a graphene oxide metamaterial; the fluid subdivision device is a plurality of horizontal grid plates provided at the ejection port, and the spacing between adjacent horizontal grid plates is greater than 10 μm; The key to this process is to set up a fluid subdivision device in front of the fluid ejection port. During the flow of the liquid, a velocity gradient difference is generated, causing the graphene oxide sheets to experience shear force in the flow channel, resulting in orderly arrangement and orientation. Specifically, the structure of the fluid subdivision device can adjust the direction, speed and pressure of the liquid flow to accurately control the arrangement of the graphene oxide sheets. In this way, the graphene oxide sheets form a primary metamaterial with a predetermined structure during the flow process, and this structure helps to improve the mechanical properties of the material. At the moment of extrusion, the edges of the graphene oxide in adjacent grids merge with each other.

[0008] (2) Reducing graphene oxide metamaterials to graphene metamaterials; (3) drying the graphene metamaterial; (4) The dried graphene metamaterial is heat treated at 300-2800°C. High temperature treatment can effectively release the residual stress between graphene sheets and improve the crystallinity and structural stability of the material. Through high temperature treatment, the arrangement of graphene sheets is further optimized, and the strength, modulus and resilience of the material are significantly improved.

[0009] Furthermore, the graphene oxide solution in step (1) is a pure graphene oxide solution or a mixed solution of graphene oxide and a polymer; the polymer is one of PAN, PAA, PVA and PVP, and the mass of graphene oxide in the solute of the graphene oxide solution is not less than 30%; the concentration of graphene oxide is 5.0 to 80.0 mg / mL.

[0010] Furthermore, the coagulation bath in step (1) is a metal salt solution or a polyamine solution, including one of calcium chloride, aluminum chloride, diamine, and triamine; the metal salt or polyamine can undergo a cross-linking reaction with graphene oxide. Generally, a high-valent metal salt solution such as calcium chloride or aluminum chloride is selected as the coagulation bath. These high-valent metal salt solutions or polyamine solutions undergo a cross-linking reaction with graphene oxide, thereby enhancing the bonding force between the sheets. This cross-linking reaction not only fixes the arrangement of the graphene oxide sheets, but also improves the structural stability of the material, laying the foundation for subsequent reduction treatment and heat treatment.

[0011] Furthermore, the reduction method in step (2) is to react in a reducing agent with a concentration of 5wt% for 5 hours; the reducing agent is one of sodium ascorbate, hydroiodic acid, hydrobromic acid, tin dichloride and hydrazine hydrate. These reducing agents can effectively reduce graphene oxide while maintaining the ordered structure of its sheets. The reduction process not only improves the conductivity of the material, but also further enhances its mechanical properties.

[0012] Furthermore, the drying method in step (3) is freeze drying or drying at room temperature and normal pressure. The reduced graphene metamaterial is placed in a freeze dryer for freeze drying. The freeze drying process can remove moisture from the material at low temperatures while avoiding structural collapse during the drying process. Through freeze drying, the three-dimensional structure of the graphene metamaterial is maintained, further improving the overall performance of the material. In addition, the reduced graphene metamaterial can also be dried at room temperature.

[0013] The preparation method of the present invention uses a plurality of horizontal grid plates to form a fluid subdivision device. The shear anchoring effect of the horizontal grid plates on graphene oxide slows down the flow rate of the graphene oxide solution near the horizontal grid plates, while the flow rate of the graphene oxide solution far away from the horizontal grid plates is faster, so that the graphene oxide solution forms a C structure when it is squeezed into the coagulation bath through the fluid subdivision device, that is, the part close to the horizontal grid plate is parallel to the horizontal grid plate, and the middle part far away from the horizontal grid plate is perpendicular to the grid. This structure enables the material to disperse and resist stress more effectively when subjected to force. Compared with closed cross-sections, open C-shaped cross-sections usually have larger fillet radii at corners, which helps to disperse stress and reduce stress concentration points, thereby reducing the risk of local buckling. Since one side of the C-shape is open, it has higher flexibility than a completely closed cross-section (such as a rectangle or a circle), and can more easily adapt to bending deformation without immediately reaching the yield point.

[0014] In addition, the size of the C-shape can be adjusted by adjusting the spacing of the horizontal grid plates, and then graphene materials with different elasticity and hardness can be designed according to needs. When the distance between the horizontal grid plates increases, the opening width of the C-shaped structure will also increase accordingly. On the contrary, if the distance between the horizontal grid plates is reduced, the C-shaped structure will be more compact. When the opening of the C-shaped structure is small, the ring structure formed by its closed part is closer to a complete circle or ellipse, which increases the overall stiffness of the structure. Therefore, C-shaped structures with smaller openings usually exhibit higher bending stiffness and lower elastic deformation capacity. On the contrary, a larger opening means that the C-shaped structure is more open, reducing the constraint between the materials, thereby reducing the overall stiffness. Such a structure is more prone to elastic deformation and is suitable for applications that require a larger deformation range.

[0015] Beneficial effects of the present invention: Under the application of the fluid subdivision device, a highly elastic material composed of C-shaped graphene sheets can be formed, thereby significantly improving the mechanical properties of the material. Reduction treatment and high temperature treatment further optimize the structure and performance of the material, making it exhibit excellent performance in high-performance applications, and provide important technical support and innovative solutions for the development of high value-added fields such as piezoresistive stress sensors and high-performance composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram of a fluid subdivision device in Example 1; Figure 2 is a cross-sectional view of Example 1; Figure 3 This is the cycle stability of Example 1. DETAILED DESCRIPTION

[0017] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0018] The raw materials used in the present invention, unless otherwise specified, are conventional commercial products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art. The concentrations described in the present invention, unless otherwise specified, are generally mass fractions.

[0019] Generally, the thickness and spacing of the grid plates used for preparing graphene by wet extrusion are no more than 5 cm.

[0020] The coagulation bath used in the present invention is a commonly used coagulation bath in the art, including but not limited to calcium chloride, aluminum chloride, diamine, and triamine. As is common knowledge in the art, the concentration of the coagulation bath is generally 1 wt % to 10 wt %.

[0021] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0022] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0024] Example 1 (1) A horizontal grid plate was used to divide the extrusion port into multiple upper and lower subdivided channels with rectangular holes of 100 μm in height. A 10 mg / mL aqueous graphene oxide solution was extruded through the subdivided channels into a calcium chloride coagulation bath. The free calcium on the graphene surface was then washed away with water multiple times to obtain a graphene oxide superstructure hydrogel. (2) immersing the graphene oxide superstructure hydrogel in step 1 in a 5 wt% sodium ascorbate solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water multiple times to obtain a gel-like graphene supermaterial; (3) freeze-drying the gel-like graphene metamaterial in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) subjecting the freeze-dried sample in step 3 to a high temperature annealing treatment at 1000°C to obtain a rectangular graphene metamaterial; After mechanical testing, the graphene metamaterial has a compressive strength of 135 KPa and a modulus of 200 KPa. After 5,000 cycles, the stress retention rate is 94%.

[0025] Example 2 (1) A horizontal grid plate was used to divide the extrusion outlet into multiple upper and lower subdivided flow channels with rectangular holes of 10 μm in height. A mixed solution of graphene oxide and PVA with a mass ratio of 5:5 was extruded through the subdivided flow channels into a diamine coagulation bath. The concentration of graphene oxide was 5 mg / mL. The diamine on the graphene surface was then washed off with water multiple times to obtain a graphene oxide superstructure hydrogel. (2) immersing the gel-like graphene oxide metamaterial in step 1 in a 5 wt% hydroiodic acid solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water for multiple times to obtain a gel-like graphene metamaterial; (3) freeze-drying the gel-like graphene metamaterial in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) subjecting the freeze-dried sample in step 3 to a high temperature annealing treatment at 2800° C. to obtain a rectangular graphene metamaterial; After mechanical testing, the graphene metamaterial's compressive strength reached 90 KPa and its modulus was 180 KPa. After 5,000 cycles, the stress retention rate was 93%.

[0026] Example 3 (1) A horizontal grid plate was used to divide the extrusion outlet into multiple upper and lower subdivided flow channels with rectangular holes of 100 μm in height. A mixed solution of graphene oxide and PAA with a mass ratio of 4:6 was extruded through the subdivided flow channels into an aluminum chloride coagulation bath. The concentration of graphene oxide was 15 mg / mL. Subsequently, the free aluminum on the graphene surface was washed away with water multiple times to obtain a graphene oxide superstructure hydrogel. (2) immersing the gel-like graphene oxide metamaterial in step 1 in a 5 wt % hydrobromic acid solution, controlling the temperature at 80 ° C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water for multiple times to obtain a gel-like graphene metamaterial; (3) freeze-drying the gel-like graphene metamaterial in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high temperature annealing treatment at 300° C. to obtain a rectangular graphene metamaterial.

[0027] Example 4 (1) A horizontal grid plate was used to divide the extrusion port into multiple upper and lower subdivided flow channels with rectangular holes of 100 μm in height. A mixed solution of graphene oxide and PAN with a mass ratio of 3:7 was extruded through the subdivided flow channels into a triamine coagulation bath. The concentration of graphene oxide was 80 mg / mL. The triamine on the surface of graphene was then washed off with water for multiple times to obtain a graphene oxide superstructure hydrogel. (2) immersing the gel-like graphene oxide metamaterial in step 1 in a 5 wt% tin dichloride solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water for multiple times to obtain a gel-like graphene metamaterial; (3) freeze-drying the gel-like graphene metamaterial in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high temperature annealing treatment at 300° C. to obtain a rectangular graphene metamaterial.

[0028] Example 5 (1) A horizontal grid plate was used to divide the extrusion port into multiple upper and lower subdivided flow channels with rectangular holes of 100 μm in height. A mixed solution of graphene oxide and PVP with a mass ratio of 5:5 was extruded through the subdivided flow channels into a calcium chloride coagulation bath. The concentration of graphene oxide was 60 mg / mL. Subsequently, free calcium on the surface of graphene was washed away with water several times to obtain a graphene oxide superstructure hydrogel. (2) immersing the gel-like graphene oxide metamaterial in step 1 in a 5 wt% hydrazine hydrate solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water for multiple times to obtain a gel-like graphene metamaterial; (3) drying the gel-like graphene metamaterial in step 2 at room temperature to remove internal moisture and ensure the integrity of the structure, thereby obtaining a dried sample; (4) The dried sample in step 3 is subjected to a high temperature annealing treatment at 300° C. to obtain a rectangular graphene metamaterial.

[0029] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A highly elastic graphene-based metamaterial, characterized in that: The invention comprises a plurality of structural units, wherein the structural units have an arched structure formed by stacking curved graphene sheets in a lateral direction; The structural units are stacked one on top of the other and fuse with each other at the interface.

2. A method for preparing a graphene-based metamaterial according to claim 1, characterized in that: The following steps are involved: (1) a fluid subdivision device is provided in front of the fluid ejection port, a graphene oxide solution is wet-extruded through the fluid subdivision device, and then pushed into a coagulation bath to obtain a graphene oxide metamaterial; the fluid subdivision device is a plurality of horizontal grid plates provided at the ejection port, and the spacing between adjacent horizontal grid plates is greater than 10 μm; (2) Reducing graphene oxide metamaterials to graphene metamaterials; (3) drying the graphene metamaterial; (4) Heat treating the dried graphene metamaterial at 300-2800°C.

3. The preparation method according to claim 2, characterized in that: The graphene oxide solution in step (1) also includes a polymer; the polymer is one of PAN, PAA, PVA and PVP, and the mass of graphene oxide in the solute of the graphene oxide solution is not less than 30%; the concentration of graphene oxide is 5.0 to 80.0 mg / mL.

4. The preparation method according to claim 2, characterized in that: The coagulation bath in step (1) is a metal salt solution or a polyamine solution, including one of calcium chloride, aluminum chloride, diamine, and triamine; the metal salt or polyamine can undergo a cross-linking reaction with graphene oxide.

5. The preparation method according to claim 2, characterized in that: The reduction method in step (2) is to react in a 5wt% reducing agent for 5 hours; the reducing agent is one of sodium ascorbate, hydroiodic acid, hydrobromic acid, tin dichloride and hydrazine hydrate.

6. The preparation method according to claim 2, characterized in that: The drying method in step (3) is freeze drying or drying at room temperature and normal pressure.

Citation Information

Patent Citations

  • Preparation method of patterned graphene flexible strain sensor

    CN109163653A

  • Method for preparing graphene-based carbon fibers at room temperature

    CN113136640A

  • Graphene material with both high strength and high toughness and preparation method thereof

    CN113151935A

  • Graphene assembly fiber as well as preparation method and application thereof

    CN114990734A

  • Applications of graphene grids in vacuum electronics

    US20150243468A1

Cited By

  • Sealing ring and preparation method thereof

    CN120027207A

  • A sealing ring and a method for manufacturing the same

    CN120027207B